Prostaglandin E-2 and the Suppression of Phagocyte Innate Immune Responses in Different Organs - Medeiros, Alexandra Ivo de [UNESP]; Peres-Buzalaf, Camila; Verdan, Felipe Fortino [UNESP]; Henrique Serezani, C. (Hindawi Publishing Corporation, 2012)
The local and systemic production of prostaglandin E-2 (PGE(2)) and its actions in phagocytes lead to immunosuppressive conditions. PGE2 is produced at high levels during inflammation, and its suppressive effects are caused by the ligation of the E prostanoid receptors EP2 and EP4, which results in the production of cyclic AMP. However, PGE(2) also exhibits immunostimulatory properties due to binding to EP3, which results in decreased cAMP levels. The various guanine nucleotide-binding proteins (G proteins) that are coupled to the different EP receptors account for the pleiotropic roles of PGE(2) in different disease states. Here, we discuss the production of PGE(2) and the actions of this prostanoid in phagocytes from different tissues, the relative contribution of PGE(2) to the modulation of innate immune responses, and the novel therapeutic opportunities that can be used to control inflammatory responses.